2019
DOI: 10.1063/1.5099051
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear oscillatory fully-developed rarefied gas flow in plane geometry

Abstract: Note: This paper is part of the special issue on Direct Simulation Monte Carlo-The Legacy of Graeme A. Bird.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
4
2
0
Order By: Relevance
“…Then, as δ is further increased G A (δ, θ) tends to a maximum at some δ (depending on θ) and it is then again decreased. It is noted that, the above behavior described for the Poiseuille coefficient amplitude is in agreement with the one reported in [117,118,130].…”
Section: Complex Poiseuille Coefficient and Macroscopic Velocitysupporting
confidence: 91%
See 2 more Smart Citations
“…Then, as δ is further increased G A (δ, θ) tends to a maximum at some δ (depending on θ) and it is then again decreased. It is noted that, the above behavior described for the Poiseuille coefficient amplitude is in agreement with the one reported in [117,118,130].…”
Section: Complex Poiseuille Coefficient and Macroscopic Velocitysupporting
confidence: 91%
“…In addition, for a specific θ, the phase angle is very close to zero at the free-molecular limit and is increased as δ is increased, tending to the maximum phase angle difference of π/2 at the viscous limit. It is noted that similar to the Poiseuille coefficient amplitude, the above remarks for the phase angle are in accordance with the ones made in [117,118,130].…”
Section: Complex Poiseuille Coefficient and Macroscopic Velocitysupporting
confidence: 88%
See 1 more Smart Citation
“…Obviously, the pumping power has two peaks within each oscillatory cycle because it consists of the product of the oscillatory flow times the oscillatory pressure gradient and its integral over one cycle is not zero in order to drive the mixture flow, although the oscillatory net flow is zero. The dependency of the mixture pumping power on the flow parameters is similar to the one observed in oscillatory single gas flow [164,128]. In general, as θ is decreased its amplitude is decreased and its phase angle lag is increased and this behavior becomes more dominant as δ is increased.…”
Section: Pressure-driven Wall Shear Stress and Pumping Powersupporting
confidence: 69%
“…Also, it has been shown that as the velocity amplitude of the oscillating wall is increased, the macroscopic quantities may contain several harmonics [161][162][163]. The corresponding nonlinear force driven flow has been recently examined with the DSMC method [164] and it is presented in Chapter 5 along with the deterministic formulation.…”
Section: Oscillatory Flows Via Kinetic Modellingmentioning
confidence: 99%